VD_FINDINFO HC / 2017 / 683 vom 17. August 2017 - VD Tribunal cantonal (2017)
FARDEAU DE LA PREUVE, PRESCRIPTION, RÉPARTITION DES FRAIS, SOCIÉTÉ COOPÉRATIVE, PART SOCIALE, SORTIE | 864 al. 2 CO, 106 al. 2 CPC (CH), 55 al. 1 CPC (CH)